Assertiveness: an analysis of national academic production (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
This study aims at identifying and characterizing the academic production of national studies on assertiveness. A systematic review was conducted based on three kinds of sources: (a) thesis and dissertations database from the Coordination for the Improvement of Higher Education Personnel (CAPES); (b) indexed journals on the Lilacs, Scielo, IndexPsi/Journals databases and Google Scholar; (c) books produced by authors who compose research groups in the behavior analysis and cognitive behavior areas. 64 studies published between 1978 and 2014 were recovered. The study categories identified in the analysis were named as: 1 – Theoretical, 2 – Applied, 3 – Characterization and/or correlations, 4 – Interventions, 5 – Construction, adaptation and validation of evaluation tools and 6 – Others. The results pointed to a predominance of the category 2 (Applied studies), followed by the 3 (Characterization and/or correlations). The analysis contributed for identifying a research agenda and gaps regarding types of studies and research focuses on assertiveness.
Keywords: assertiveness; national studies; literature review